Controllability for discrete event systems modelled in VeriJ. (1st January 2014) - Zhang, Yan; Bérard, Béatrice; Hillah, Lom Messan; Kordon, Fabrice; Thierry-Mieg, Yann
Existing tools for controllability checking mostly apply to abstract formalisms like finite automata or Petri nets. To avoid costly building of low-level formal models for large complex systems, we propose a programming language called VeriJ, a subset of Java with additional constructs dedicated to supervisory control, to model these systems in a familiar and friendly development environment. We provide a prototype tool chain, based on model transformation and pushdown automata, to automatically transform a system described in VeriJ into a labelled transition system (LTS). A controllability engine for this LTS is then integrated to the tool. To limit the state space explosion problem, we also add several mechanisms including garbage collection, abstraction, state compression, and partial exploration. Our approach, illustrated with a VeriJ model of the Nim game, shows that it is possible to combine: 1) the benefits resulting from using mature Java development environments; 2) performances comparable to those of existing tools.